Desert Spirituality in 17th and 18th Century French Calvinism - MacGregor, Kirk R. (Religious studies and theology, 2007)
Between the 1685 Revocation of the Edict of Nantes and the 1735 partial renewal of Protestant toleration, the Huguenots choosing to remain in France were forced to clandestinely practice their religion in the wasteland, or désert, of the Cévennes. Understood within an Old Testament interpretive framework, the Huguenots perceived themselves as the new Israel, which identification was reinforced by their adoption of a covenant theology recognizing only one people of God. Moreover, the decentered character of the désert facilitated direct and universal numinous encounter by its occupants, thereby dissolving traditional boundaries as well as empowering charismata among all those seized by the Spirit. Accordingly, these désert episodes proved instrumental in forging a new Huguenot identity, onto which community members tenaciously clung even following their readmission into French civic affairs.